인공수정체 탈구 수술 후 발생한 안압상승의 장기적 임상 경과 - 나동규(Dong Gyu Na), 박새미(Sae Mi Park) (Daihan angwa haghoi jabji, 2025)
목적: 인공수정체 탈구는 백내장수술 후 발생할 수 있는 비교적 흔한 합병증 중 하나로, 인공수정체 탈구에 대한 수술 후 안압이 상승하는 경우가 있다. 본 연구는 인공수정체 탈구 수술 후 안압이 상승한 환자들의 장기적인 임상 경과를 조사하였다. 대상과 방법: 2020년 1월부터 2022년 12월까지 본원 1명의 망막전문의로부터 인공수정체 탈구 수술을 받은 총 65명의 환자를 대상으로 후향적으로 의무기록을 분석하였다. 수술 후 1주일 이내 고안압군(≥22 mmHg)과 정상안압군(<22 mmHg)을 비교하고, 수술 후1년 이상 안압을 추적하여 녹내장 발생 비율을 조사하였다. 결과: 인공수정체 탈구 수술 후 고안압군 48명과 정상안압군 17명 간의 탈구 유형에 따른 통계적 차이는 없었다(p=0.254). 수술 후1달째 평균 안압은 고안압군에서 18.6 ± 5.9 mmHg, 정상안압군에서 14.3 ± 4.0 mmHg로 유의미한 차이를 보였으나(p<0.001), 1년째평균 안압은 고안압군 15.3 ± 3.7 mmHg, 정상안압군 16.2 ± 5.0 mmHg로 차이가 없었다(p=0.696). 안압약 사용은 수술 후 1주일째고안압군에서 평균 1.2 ± 0.8개였고, 정상안압군에서는 0.2 ± 0.7개로 유의미한 차이를 보였으나(p<0.001), 마지막 추적 관찰 시에는고안압군 0.5 ± 0.9개, 정상안압군 0.2 ± 0.6개로 차이가 없었다(p=0.227). 결론: 인공수정체 탈구 수술 후 초기에는 안압상승을 유발할 수 있으나, 장기적으로는 호전되는 경향을 보였다. Purpose: Intraocular lens (IOL) dislocation is a relatively common complication after cataract surgery, leading to an increase in intraocular pressure (IOP) following IOL dislocation surgery. This study investigated the long-term clinical course of patients who experienced IOP elevation after IOL dislocation surgery. Methods: This retrospective study analyzed 65 patients who underwent IOL dislocation surgery by a single retinal specialist from January 2020 to December 2022. The patients were divided into high (≥ 22 mmHg) and normal (< 22 mmHg) IOP groups based on the IOP within 1 week of surgery. IOP was tracked for over a year to assess the incidence of glaucoma. Results: There were no significant (p = 0.254) differences in dislocation types between the high (48 patients) and normal (17 patients) IOP groups. One month after surgery, the mean IOP was 18.6 ± 5.9 mmHg in the high IOP group and 14.3 ± 4.0 mmHg in the normal IOP group (p < 0.001). At 1 year, the values were 15.3 ± 3.7 and 16.2 ± 5.0 mmHg, respectively (p = 0.696). One week after surgery, the high IOP group used 1.2 ± 0.8 IOP-lowering medications compared to 0.2 ± 0.7 in the normal IOP group (p < 0.001). At the final follow-up, medication use was 0.5 ± 0.9 and 0.2 ± 0.6, respectively (p = 0.227). Conclusions: Although IOP elevation may occur following IOL dislocation surgery, it tends to improve over time. KCI Citation Count: 0